1987
DOI: 10.2165/00003088-198712050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions of Cimetidine 1987

Abstract: The number of studies on drug interactions with cimetidine has increased at a rapid rate over the past 5 years, with many of the interactions being solely pharmacokinetic in origin. Very few studies have investigated the clinical relevance of such pharmacokinetic interactions by measuring pharmacodynamic responses or clinical endpoints. Apart from pharmacokinetic studies, invariably conducted in young, healthy subjects, there have been a large number of in vitro and in vivo animal studies, case reports, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(79 citation statements)
references
References 176 publications
2
76
0
1
Order By: Relevance
“…For an orally administered drug which is cleared predominantly by hepatic metabolism, AUC is related to the dose administered, the fraction of administered dose which is absorbed from the gut into the hepatic portal vein (FG), the plasma unbound fraction of the drug (fu) and its intrinsic clearance (CLint) (Somogyi & Muirhead, 1987). Previous investigations with ibuprofen indicated that a large fraction of an orally administered dose is recovered in urine as unchanged drug and metabolites (Lockwood & Wagner, 1982;Mills et al, 1973).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For an orally administered drug which is cleared predominantly by hepatic metabolism, AUC is related to the dose administered, the fraction of administered dose which is absorbed from the gut into the hepatic portal vein (FG), the plasma unbound fraction of the drug (fu) and its intrinsic clearance (CLint) (Somogyi & Muirhead, 1987). Previous investigations with ibuprofen indicated that a large fraction of an orally administered dose is recovered in urine as unchanged drug and metabolites (Lockwood & Wagner, 1982;Mills et al, 1973).…”
Section: Resultsmentioning
confidence: 99%
“…Because ibuprofen's spectrum of adverse reactions includes gastrointestinal side-effects (Fowler et al 1980), concurrent administration with anti-ulcer drugs, such as the histamine H2-receptor antagonist cimetidine, is not uncommon. Cimetidine is known to interact with a large number of drugs by inhibiting their oxidative metabolism (Somogyi & Muirhead, 1987). Because oxidative biotransformation plays such an important role in the disposition of ibuprofen, it seems a likely candidate for a pharmacokinetic interaction with cimetidine.…”
Section: Introductionmentioning
confidence: 99%
“…Cimetidine has also been shown to decrease the renal clearance of ranitidine, metformin, triamterene and flecainide (Somogyi & Muirhead, 1987) or of procainamide and its active metabolite N-acetylprocainamide (Somogyi et al, 1983), by competing with them for the active transport system for bases. In the present study we found no suggestion of excretory interaction between cimetidine and the parent drug or its two metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…It is also used for anaesthetic premedication to lower the incidence of the acid aspiration syndrome (Dundee et al, 1981;Manchikanti et al, 1982). However, cimetidine has also been shown to inhibit the elimination of many other drugs (Somogyi & Muirhead, 1987), including lignocaine, which is structurally related to bupivacaine (Kim & Tasch, 1986;Feely et al, 1982;Knapp et al, 1983;Bauer et al, 1984). All of the amide local anaesthetic agents are metabolized primarily in the liver (Covino, 1984) and cimetidine is capable of impairing drug oxidation at this site.…”
Section: Introductionmentioning
confidence: 99%
“…Cimetidine, a histamine H2-receptor antagonist, is a competitive inhibitor of the hepatic cytochrome P-450 mixed function oxidase system (Somogyi & Gugler, 1982;Somogyi & Muirhead, 1987). Ranitidine and famotidine do not inhibit this system (Cate et al, 1986;Locniskar et al, 1986).…”
Section: Introduction Methodsmentioning
confidence: 99%